2016
DOI: 10.1038/nchem.2640
|View full text |Cite
|
Sign up to set email alerts
|

Imaging quantum stereodynamics through Fraunhofer scattering of NO radicals with rare-gas atoms

Abstract: Stereodynamics describes how the vector properties of molecules, such as the directions in which they move and the axes about which they rotate, affect the probabilities (or cross-sections) of specific processes or transitions that occur on collision. The main aspects of stereodynamics in inelastic atom-molecule collisions can often be understood from classical considerations, in which the particles are represented by billiard-ball-like hard objects. In a quantum picture, however, the collision is described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 51 publications
(63 reference statements)
0
58
0
Order By: Relevance
“…We found that the angular momenta of two excited molecules indeed become quantum entangled, leading to a violation of Bell's inequalities that may in principle be probed experimentally (see Supplementary section: Entanglement). This entanglement occurs especially for the Fraunhofer diffraction oscillations in the differential cross sections at small scattering angles (11).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found that the angular momenta of two excited molecules indeed become quantum entangled, leading to a violation of Bell's inequalities that may in principle be probed experimentally (see Supplementary section: Entanglement). This entanglement occurs especially for the Fraunhofer diffraction oscillations in the differential cross sections at small scattering angles (11).…”
Section: Discussionmentioning
confidence: 98%
“…State-to-state cross sections (5), steric effects (?, 6), as well as vector correlations between pre and post-collision properties (8)(9)(10) can be precisely measured, and in general show excellent agreement with predictions based on full quantum mechanical calculations. During the last decades, this wealth of experimental and theoretical studies has revealed how energy and angular momentum is transferred between the collision partners, although surprising discoveries continue to be made (11). Sophisticated qualitative and intuitive models have been developed that explain general trends in the scattering cross sections, which can also be determined quantitatively by near-exact quantum mechanical treatments.…”
mentioning
confidence: 99%
“…A number of techniques for the generation of cold molecules has been developed [1-5] among which Stark deceleration is one of the most important [3,[6][7][8]. This method finds a broad range of applications in spectroscopy [9][10][11][12], collision-dynamics studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26] and trap loading experiments [27][28][29][30][31][32][33]. The principle of Stark deceleration has been well documented [2,3], and a number of operation schemes have been developed for the optimization of Stark-decelerated molecular beams in different types of experiments [34][35][36][37].…”
Section: Reviewmentioning
confidence: 99%
“…Of particular interest are resonances of the collision cross section as a function of the collision energy [7][8][9][10]. The position and shape of these resonances are very sensitive to the exact shape of the PES and thus serve as precise tests of our understanding of intermolecular forces.The ability to control the velocity of molecules using time-varying electric fields has allowed studies of inelastic collisions of OH and NO molecules with rare gas atoms at low collision energies [11][12][13][14]. Using cryogenically cooled beams under a small (and variable) crossing angle, inelastic collisions of O 2 and CO with H 2 and helium at energies between 5 and 30 K have been studied [15].…”
mentioning
confidence: 99%
“…The ability to control the velocity of molecules using time-varying electric fields has allowed studies of inelastic collisions of OH and NO molecules with rare gas atoms at low collision energies [11][12][13][14]. Using cryogenically cooled beams under a small (and variable) crossing angle, inelastic collisions of O 2 and CO with H 2 and helium at energies between 5 and 30 K have been studied [15].…”
mentioning
confidence: 99%